Critical Synthesis Package: Central Venous Line Simulator Checklist'subclavian Approach - Jorie Colbert-Getz (Association of American Medical Colleges, 2013)
Abstract This Critical Synthesis Package contains: (1) a Critical Analysis of the psychometric properties and application to health sciences education for the Central Venous Line Simulator Checklist'subclavian Approach (CVLS), and (2) a copy of the CVLS instrument developed by Grace Huang, MD. The CVLS is designed to measure residents' competency in central venous catheter (CVC) insertion. Checklist items were developed by conducting a literature review and were categorized as major or minor by the authors. A modified Delphi process was then conducted with experts. There was a high degree of internal consistency for checklists scores, but interrater reliability was low. A standard-setting exercise (Angoff) was conducted to determine borderline and competent performance. The checklist appears to be able to assess competent performance, but not borderline performance. Validity evidence is limited to testing on internal medicine residents performing simulated CVC insertions in Boston while being rated by two of the authors. Validity evidence could be improved by seeing how other internal medicine residents perform with the checklist and more internal consistency of raters needs to be explored with raters other than the authors.